1997
DOI: 10.4088/jcp.v58n0607b
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine Treatment of Refractory Bipolar Disorder

Abstract: Lamotrigine Treatment of Refractory Bipolar DisorderSir: Lamotrigine represents a new class of anticonvulsant for the treatment of adult patients with refractory partial seizures. Lamotrigine is chemically unrelated to carbamazepine and phenytoin, but is thought to act at voltage-sensitive sodium channels to stabilize neuronal membranes and inhibit transmitter release, principally glutamate and aspartate, 1 similar to the inhibition of neuronal activity produced by phenytoin and carbamazepine.2 Further, lamotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…CBZ, commonly used in the treatment of both partial and generalized epilepsies, is now also frequently used in psychiatry for the treatment of aggressive behavior and bipolar disease (71,99,101). Several recent papers have described mood-stabilizing properties of LTG in patients with treatment-refractory bipolar disease (102)(103)(104). These effects have recently been confirmed in randomized, controlled studies.…”
Section: General Approachmentioning
confidence: 87%
“…CBZ, commonly used in the treatment of both partial and generalized epilepsies, is now also frequently used in psychiatry for the treatment of aggressive behavior and bipolar disease (71,99,101). Several recent papers have described mood-stabilizing properties of LTG in patients with treatment-refractory bipolar disease (102)(103)(104). These effects have recently been confirmed in randomized, controlled studies.…”
Section: General Approachmentioning
confidence: 87%
“…In particular, lamotrigine might disorder, having 6 schizomanic episodes since age 21, with full remission in between. Originally, the disorder started with a severe depresbe helpful in treatment-refractory bipolar disorder [4][5][6], sion and a suicide attempt in 1986. The patient continuously took rapid-cycling bipolar disorder [7,8], bipolar depression lithium since 1993, the last schizomanic episodes were 3/97 and 9/97.…”
Section: And In Combination Withmentioning
confidence: 99%
“…Several investigations have suggested that the new antiepileptic drug lamotrigine is efficacious in bipolar disorder, particularly in rapid cycling [10–14] and bipolar depression [15]. A randomized, placebo controlled double blind study indicated a good antidepressant effect of 50 and 200 mg of lamotrigine in patients with bipolar depression [15].…”
Section: Introductionmentioning
confidence: 99%